PENGARUH KONSENTRASI KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN - Andi Wawo (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The objective of this research will test the effect of concentrated ownership on the company’s performance. Especially, this research will test the effect of concentated ownership on the company’s performance. Concentated ownership is immediated ownership in company. Immediated ownership data are proportion of biggest shareholder in company. This research samples are public companies listed on the Indonesian Stock Exchange for the period in 5 years which is in period of 2003 to 2007 with exception of bank and financial institutions. Hypothesis test by method which is used by Fang and Wong (2002) with concentrate ownership, while control variable in this research use market to book ratio, leverage, and fixed effect. The result research can be summarized as following; Concentrated ownership at immediate level has a negative effect the company’s performance at cut-off 10%, 20% and 30% but concentrated ownership does not has effect the company’s performance at level 40% and 50%. This result supported by sensitivity test on cut-off point 20%, 30%, 40% and 50% are not effect.